1996
DOI: 10.1103/physrevd.54.7599
|View full text |Cite
|
Sign up to set email alerts
|

Does a nonzero tunneling probability imply particle production in time-independent classical electromagnetic backgrounds?

Abstract: In this paper, we probe the validity of the tunnelling interpretation that is usually called forth in literature to explain the phenomenon of particle production by time independent classical electromagnetic backgrounds. We show that the imaginary part of the effective lagrangian is zero for a complex scalar field quantized in a time independent, but otherwise arbitrary, magnetic field. This result implies that no pair creation takes place in such a background. But we find that when the quantum field is decomp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
22
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 23 publications
5
22
0
Order By: Relevance
“…The instanton interpretation thus resolves the contradiction between the effective action and the canonical method raised in Ref. [49]. Our result also agrees with that by Dunne and Hall, who showed that the imaginary part of the effective action vanishes for the static magnetic field considered above and therefore neither bosons nor fermions are produced in pairs [50,51].…”
Section: Magnetic Fieldssupporting
confidence: 91%
See 2 more Smart Citations
“…The instanton interpretation thus resolves the contradiction between the effective action and the canonical method raised in Ref. [49]. Our result also agrees with that by Dunne and Hall, who showed that the imaginary part of the effective action vanishes for the static magnetic field considered above and therefore neither bosons nor fermions are produced in pairs [50,51].…”
Section: Magnetic Fieldssupporting
confidence: 91%
“…As the nonzero transmission probability through potential wells is the result without any finite instanton, the instanton interpretation excludes the possibility of pair-production by a static localized magnetic field in the canonical method raised in Ref. [49]. Therefore we conclude that any static magnetic field does not lead to pair-production and the canonical method equipped with the instanton interpretation is compatible with the effective action method [17,49,50].…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…As an example, an elegant treatment of the axial anomaly in an external electromagnetic background, which appeals to a similar physical mechanism as above, is given in [15,32]. Fluctuations in expectation values can be calculated using (17). Consider fluctuations of some quantityÂ(t 1 ) in the "evolved vacuum."…”
Section: Expectation Valuesmentioning
confidence: 99%
“…We also show how our particle definition can be expressed in more conventional terms by discussing its relation to the method of Hamiltonian diagonalisation. Our definition consistently combines the conventional "Bogoliubov coefficient method" with the "tunnelling method," resolving the gauge inconsistencies [17] that trouble each of these methods. A retrospective overview is presented in Section 6.…”
Section: Introductionmentioning
confidence: 99%